Occurrence and diversity of clinically important Vibrio species in the aquatic environments of Georgia - Tamari eKokashvili; Chris eWhitehouse; Ana eTskhvediani; Christopher John Grim; Christopher John Grim; Tinatin eElbakidze; Nino eMitaishvili; Nino eJanelidze; Ekaterine eJaiani; Bradd eHaley; Nino eLashkhi; Anwar eHuq; et al. (Frontiers in Public Health, 2015)
Among the more than 70 different Vibrio species inhabiting marine, estuarine, and freshwater ecosystems, 12 are recognized as human pathogens. The warm subtropical climate of the Black Sea coastal area and inland regions of Georgia likely provides a favorable environment for various Vibrio species. From 2006 to 2009, the abundance, ecology, and diversity of clinically important Vibrio species were studied in different locations in Georgia and across seasons. Over a 33-month period, 1,595 presumptive Vibrio isolates were collected from the Black Sea (n=657) and freshwater lakes around Tbilisi (n=938). Screening of a subset of 440 concentrated and enriched water samples by PCR-electrospray ionization/mass spectrometry (PCR-ESI/MS) detected the presence of DNA from eight clinically important Vibrio species: V. cholerae, V. parahaemolyticus, V. vulnificus, V. mimicus, V. alginolyticus, V. harveyi, V. metschnikovii, and V. cincinnatiensis. Almost ninety percent of PCR/ESI-MS samples positive for Vibrio species were collected from June through November. Three important human pathogenic Vibrio species (V. cholerae, V. parahaemolyticus, and V. vulnificus) were detected in 62.8%, 37.8%, and 21.4% of samples testing positive for vibrios, respectively. The results of these activities suggest that natural reservoirs for human-pathogenic Vibrios exist in Georgian aquatic environments. Water temperature at all sampling sites was positively correlated with the abundance of clinically important Vibrio spp. (except V. metschnikovii) and salinity was correlated with species composition at particular Black Sea sites as well as inland reservoirs.